The Effects of Superstatistics Properties on Hot Plasma - Dilmi, S.; Khalfaoui, F.; Boumali, A. (Engineering, Technology & Applied Science Research, 2022)
The electron impact ionization is a crucial atomic process in the collisional radiative model and the study of ionization balance. The superstatistics theory, which was originally proposed for the study of non-equilibrium complex systems, has recently been extended to studies of small systems interacting with a finite environment due to their interesting statistical behavior. This paper introduces the superstatistics formalism in the case of ionization rates with different values of the dynamical parameter q and shows how it affects the calculation of the ionization rates for Li+. Moreover, the distribution function for the effective Boltzmann factor of superstatistics was swapped.